2020
DOI: 10.3389/fmars.2020.00406
|View full text |Cite
|
Sign up to set email alerts
|

Exploring New Frontiers in Marine Radioisotope Tracing – Adapting to New Opportunities and Challenges

Abstract: Radioisotopes have been used in earth and environmental sciences for over 150 years and provide unique tools to study environmental processes in great detail from a cellular level through to an oceanic basin scale. These nuclear techniques have been employed to understand coastal and marine ecosystems via laboratory and field studies in terms of how aquatic organisms respond to environmental stressors, including temperature, pH, nutrients, metals, organic anthropogenic contaminants, and biological toxins. Glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 164 publications
(173 reference statements)
0
5
0
Order By: Relevance
“…(2) measurement of the biokinetics of contaminants over the long term; and (3) distinction between foods from sources of contaminants that are difficult to investigate using standard analytical techniques [38]. Additionally, nuclear engineering facilitates experiments using concentrations of contaminants that are comparable to those found in natural waters [39].…”
Section: Resultsmentioning
confidence: 99%
“…(2) measurement of the biokinetics of contaminants over the long term; and (3) distinction between foods from sources of contaminants that are difficult to investigate using standard analytical techniques [38]. Additionally, nuclear engineering facilitates experiments using concentrations of contaminants that are comparable to those found in natural waters [39].…”
Section: Resultsmentioning
confidence: 99%
“…A complete review of this kind of studies, with emphasis on the need for non-destructive studies can be found in Ref. [3]. In fact, we plan to use a nondestructive method, putting the individuals inside a set-up and measuring the amount of 45 Ca using ad-hoc nuclear instrumentation.…”
Section: Radiotracers For the Study Of Marine And Oceanic Ecosystems ...mentioning
confidence: 99%
“…Gamma-ray spectrometry is the ideal technique for quantifying the activity concentration of radionuclides (Cresswell et al, 2017(Cresswell et al, , 2020Joel et al, 2017). Care must be taken to interpret the reading of radioactivity relative to where the gamma measurement is positioned on the piece of infrastructure e.g.…”
Section: Elemental and Radiometric Analyses Of Petroleum Scale And Norm Componentsmentioning
confidence: 99%
“…Performing laboratory studies by exposing a variety of marine species to infrastructure-associated NORM contaminants will create refined estimates of contaminant bioavailability, radiation dose and subsequent assessments of effects from NORM and IR, combined with metals. Radiotracing techniques can provide new perspectives on the pathways and rates of uptake (e.g., bioaccumulation) and biomagnification processes of radioactive and non-radioactive contaminants (Cresswell et al, 2020;Lanctôt et al, 2017). Laboratory studies are needed to investigate the radiation-induced effects from NORM contaminants associated with petroleum scale.…”
Section: Direct Organism Exposure Assessment Scenariosmentioning
confidence: 99%